Agenesis of gallbladder and multiple anomalies of the biliary tree in a patient with portal thrombosis: A case report - Yusuf BAYRAKTAR,; H. Yasemin BALABAN,; Serap ARSLAN,; Ferhun BALKANCI, (Turkish Journal of Gastroenterology, 2019)
-